The combined decision model for selecting and prioritizing research and development projects - (:unkn) unknown (My University, 2005)
In this study, a combined decision model for selecting and prioritizing Research and Development Projects is proposed. The proposed model implements both the efficiency and feasibility analysis by using the qualitative and the quantitative information in the same model. In order to determine the efficient and feasible projects among the alternative R&D projects, recent mathematical methods such as Data Envelopment Analysis (DEA), Analytic Hierarchy Process (AHP). Value Tree Analysis are implemented and combined in the proposed model. © 2005 IEEE.